Personalized Hip and Knee Joint Replacement 2020
DOI: 10.1007/978-3-030-24243-5_21
|View full text |Cite
|
Sign up to set email alerts
|

Combined Partial Knee Arthroplasty

Abstract: Arthrosis commonly affects a single compartment of the knee, but may present with two or even three compartments affected. Wear to the medial tibiofemoral compartment is ten times more common than that in the lateral tibiofemoral compartment; primary patellofemoral joint (PFJ) arthrosis is least common [1, 2]. Bicompartmental disease is present in 59% of those with gonarthrosis [3]. In one study, 40% of patients over 50 years old with knee pain had radiographic evidence of combined medial compartment and PFJ w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Combined partial knee arthroplasty (CPKA), the implantation of two PKAs within the same knee, offers a cruciate-sparing, higher functioning alternative to TKA, when at least one compartment is preserved [20][21][22][23][24][25][26][27]. Bicompartmental arthroplasty (BCA), the combination of a patellofemoral arthroplasty (PFA) with either a medial (BCA-M) or lateral (BCA-L) UKA, preserves the unaffected tibiofemoral compartment, meniscus and cruciate ligaments, whilst bi-unicondylar arthroplasty (Bi-UKA), the combination of UKA-M and UKA-L, spares the healthy patellofemoral joint and the cruciate ligaments [20,28]. However, little is known of knee anterior-posterior (A-P) stability following CPKA.…”
Section: Introductionmentioning
confidence: 99%
“…Combined partial knee arthroplasty (CPKA), the implantation of two PKAs within the same knee, offers a cruciate-sparing, higher functioning alternative to TKA, when at least one compartment is preserved [20][21][22][23][24][25][26][27]. Bicompartmental arthroplasty (BCA), the combination of a patellofemoral arthroplasty (PFA) with either a medial (BCA-M) or lateral (BCA-L) UKA, preserves the unaffected tibiofemoral compartment, meniscus and cruciate ligaments, whilst bi-unicondylar arthroplasty (Bi-UKA), the combination of UKA-M and UKA-L, spares the healthy patellofemoral joint and the cruciate ligaments [20,28]. However, little is known of knee anterior-posterior (A-P) stability following CPKA.…”
Section: Introductionmentioning
confidence: 99%
“…The functional outcomes and patient reported outcome metrics (PROMs) associated with CPKA in the staged setting (Fig. 2 ) are not known [ 12 ]. This study aimed to compare the post-operative gait and patient reported outcomes of staged CPKA to those of healthy controls and primary TKA subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 99 patients underwent unicompartmental knee arthroplasty (UKA), seven total knee arthroplasty (TKA), seven bicompartmental arthroplasty (BCA), two bi-unicondylar arthroplasty (Bi-UKA), and one patellofemoral arthroplasty (PFA). 11,12 Data collection and statistical analysis. The distribution of OKS, EQ-5D, and MET scores were analyzed and assessed for skewness, kurtosis, and ceiling and floor effects.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 99 patients underwent unicompartmental knee arthroplasty (UKA), seven total knee arthroplasty (TKA), seven bicompartmental arthroplasty (BCA), two bi-unicondylar arthroplasty (Bi-UKA), and one patellofemoral arthroplasty (PFA). 11 , 12 …”
Section: Methodsmentioning
confidence: 99%